2012
DOI: 10.1007/s00705-012-1277-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and recrudescent infection in cattle following natural infection with Middle Point orbivirus

Abstract: Middle Point orbivirus (MPOV) is a recently described Australian arbovirus, related to Yunnan orbivirus from China. Analysis of genetic variation within the major serotype gene of MPOV isolates collected from sentinel cattle has identified eight co-circulating strains. The pattern of strain isolation from individual animals during the study period was consistent with an interpretation of persistent MPOV infection of up to five months, featuring episodes of quiescence (below levels required for virus isolation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…It has been speculated that when the humoral immune response of the host is weak or if the virus in the immune complex is not completely neutralized, mosquitoes biting these vertebrate hosts may be infected, even with low frequency [ 76 ]. This possibility is compatible with the observation that cattle naturally infected with Middle Point orbivirus had prolonged viremia (up to 15 weeks) most frequently in hosts with low antibody levels [ 77 ]. Interestingly, Kyasanur Forest disease virus was re-isolated from the brains and liver of 14 of 18 mice demonstrating no neutralizing antibodies as long as 246 days after intracerebral or intraperitoneal inoculation [ 78 ].…”
Section: Problemssupporting
confidence: 87%
“…It has been speculated that when the humoral immune response of the host is weak or if the virus in the immune complex is not completely neutralized, mosquitoes biting these vertebrate hosts may be infected, even with low frequency [ 76 ]. This possibility is compatible with the observation that cattle naturally infected with Middle Point orbivirus had prolonged viremia (up to 15 weeks) most frequently in hosts with low antibody levels [ 77 ]. Interestingly, Kyasanur Forest disease virus was re-isolated from the brains and liver of 14 of 18 mice demonstrating no neutralizing antibodies as long as 246 days after intracerebral or intraperitoneal inoculation [ 78 ].…”
Section: Problemssupporting
confidence: 87%
“…A real-time reversetranscription polymerase chain reaction (RT-PCR) assay was developed for MPOV, which showed that more than 150 virus isolates obtained from cattle between 1994 and 2006 were MPOV isolates (9). YUOV (isolate MPOV) infections have been shown to persist in cattle for up to five months with periods of quiescence, followed by recrudescence of the viral titre (10).…”
Section: Yunnan Orbivirusmentioning
confidence: 99%
“…In northern Australia, orbiviruses are highly prevalent [ 3 , 4 , 5 , 6 ]. In addition to the midge-transmitted and agriculturally significant bluetongue virus, a number of mosquito-borne orbiviruses are also detected in this region [ 4 , 6 , 7 , 8 ]. Middle Point orbivirus and Stretch Lagoon orbivirus are often isolated during mosquito or animal sera screening.…”
Section: Introductionmentioning
confidence: 99%